Statement on chronotherapy for the treatment of hypertension: consensus document from the Korean society of hypertension - Sungha Park; Sang-Hyun Ihm; In-Jeong Cho; Dae-Hee Kim; Jae Hyeong Park; Woo-Baek Chung; Seonghoon Choi; Hae Young Lee; Hyeon Chang Kim; Il Suk Sohn; Eun Mi Lee; Ju Han Kim; et al. (BMC, 2023)
Abstract Nocturnal blood pressure (BP) has been shown to have a significant predictive value for cardiovascular disease. In some cases, it has a superior predictive value for future cardiovascular outcomes than daytime BP. As efficacy of BP medications wanes during nighttime and early morning, control of nocturnal hypertension and morning hypertension can be difficult. As such, chronotherapy, the dosing of BP medication in the evening, has been an ongoing topic of interest in the field of hypertension. Some studies have shown that chronotherapy is effective in reducing nocturnal BP, improving non dipping and rising patterns to dipping patterns, and improving cardiovascular prognosis. However, criticism and concerns have been raised regarding the design of these studies, such as the Hygia study, and the implausible clinical benefits in cardiovascular outcomes considering the degree of BP lowering from bedtime dosing. Studies have shown that there is no consistent evidence to suggest that routine administration of antihypertensive medications at bedtime can improve nocturnal BP and early morning BP control. However, in some cases of uncontrolled nocturnal hypertension and morning hypertension, such as in those with diabetes mellitus, chronic kidney disease, and obstructive sleep apnea, bedtime dosing has shown efficacy in reducing evening and early morning BP. The recently published the Treatment in Morning versus Evening (TIME) study failed to demonstrate benefit of bedtime dosing in reducing cardiovascular outcomes in patients with hypertension. With issues of the Hygia study and negative results from the TIME study, it is unclear at this time whether routine bedtime dosing is beneficial for reducing cardiovascular outcomes.